EFFORTS TO IMPROVE PERFORMANCE IN MANAGING REGIONAL FINANCE THROUGH HUMAN RESOURCES, ORGANIZATIONAL CULTURE AND ORGANIZATIONAL COMMITMENT - Agung Widhi Kurniawan; Deddy Ibrahim Rauf; Hery Maulana Arif (Journal Management & Economics Review (JUMPER), 2023)
The purpose of this study was to examine the effect of human resource quality, organizational commitment, and organizational culture on regional financial management performance. Research method. The population of this study were employees of the Regional Revenue Office (Dispenda) of Mataram City, totaling 85 people. The data collection technique used a questionnaire. Data analysis using multiple linear regression. The results showed that the quality of human resources, organizational commitment, and organizational culture had a significant positive effect on employee performance at the Mataram City Expenditure Department. In general, efforts are still needed to optimize the components of employee quality, organizational commitment, and organizational culture in order to have a domino effect on employee performance at the Mataram City Dispenda.